METHOD OF CREATING AN INFORMATION SYSTEM FOR MONITORING INFECTIOUS PATIENTS (Computer systems and information technologies, 2023)
In the context of the COVID-19 pandemic, infectious disease information systems are widely used and promoted to prevent the spread of the pandemic (mainly in the form of mobile applications). Many countries have offered their apps to improve contact tracing and thus reduce the number of infections. However, the level of adoption of such applications has been and remains relatively low, which, obviously, given their massive use and effectiveness, has been largely influenced by issues related to privacy and anonymity, as well as the perception of potential users of the price-benefit ratio. Thus, the task of creating information systems for monitoring infectious patients is still relevant today. Therefore, our study is devoted to the development of a method and an information system for monitoring infectious patients.The article develops a method for creating an information system for monitoring infectious patients, which, unlike the known ones, is based on intelligent analysis of data on the geolocation of patients and contact persons, and provides the ability to design an information system for controlling infectious patients. The purpose of the information system for monitoring infectious patients is to prevent the spread of epidemics and pandemics by tracking patient contacts and reducing the number of infections. The tasks of the information system for monitoring infectious patients are to track the self-isolation of infectious patients and their contacts, identify the most "infected" buildings, districts, cities, etc. based on intelligent analysis of data on infectious patients and their contacts.The designed mobile-oriented information system for monitoring infectious patients can be used to prevent the spread of the pandemic by tracking contacts and reducing the number of infections. The design of screen forms, reports, implementation, testing and commissioning of the information system for monitoring infectious patients will be carried out by the authors in the course of their further research.
Keywords: information system; control of infectious patients; method of creating an information system; data mining